The Computability of the World How Far Can Science Take Us? - Küppers, Bernd-Olaf (The Frontiers Collection,, 2018)
In this thought-provoking book Küppers, an internationally renowned physicist, philosopher and theoretical biologist, addresses a number of science's deepest questions: Can physics advance to the origin of all things and explain the unique phenomena of life, time and history? Are there unsolvable enigmas of the world? How did life originate? Is language a general phenomenon of Nature? What is time? Is it possible to express the history of the world in formulae? Where is science leading us? These and other provocative questions essential for a deeper understanding of the world are treated here in a refreshing and stimulating manner.